Semantic Networks and socio-emotional skills in teachers - Torres Valencia, Verónica (2023)
Natural Semantic Networks, as methodological tools, allow us to recover an understand the meanings that certain groups have with respect to a given social object. In this sense, teachers are the study population in topics that became relevant in the face of the ravages caused by the pandemic on emotional well-being, such as the importance of developing and putting into practice socio-emotional skills in the different areas where it is developed. The purpose of this document is to carry out a systematic descriptive theoretical review, from 1981 to 2022, of original studies carried out in Latin América, with a qualitative approach, on the relevance of Natural Semantic Networks as a methodological strategy to approach the meaning that teachers of socioemotional competencies. It is concluded that, until now, the use of Natural Semantic Networks does not exist to recover meanings of socio-emotional competencies in teachers, only approximations with constructs derive from them. The contribution of the article affects in a practical way, in the elaboration of programs aimed at the development of socio-emotional competences in the teacher, from the meanings they have on the subject, to strengthen their professional development in the task of training students of various educational levels.